Contemporary restructuring trends in European multinational corporations: rationale and impact on labour and workers' participation. Issue 4 (13th July 2020) - Dörrenbächer, Christoph; Geppert, Mike; Hoffmann, Aline
Abstract : Purpose: This paper addresses the so far hardly understood contemporary restructuring trends in European Multinational corporations (MNCs), their rationales and their labour-related implications. Design/methodology/approach: The paper is based on a systematic evaluation of academic and non-academic literature, as well as on more than 30 in-depth interviews with academic experts, management consultants, trade union consultants and workers' representatives. Findings: European MNCs continue to grow bigger, mostly through debt financed mergers and acquisitions. This triggers intensive cross-border standardization and reorganization activities that most prominently materialize as a sustained move towards global factories; a new wave of cross-border standardization in Human Resource Management, information technology and Big Data-driven, as well as compliance-induced reorganization measures. Originality/value: This paper is the first to empirically map contemporary restructuring trends in European MNCs in a comprehensive way. Moreover, it addresses the managerial rationale underlying these restructuring trends. Based on these insights the paper assesses labour related implications that are both positive and negative.